2023
DOI: 10.1128/spectrum.04733-22
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Modulates Metabolic Landscape of Bacteroidetes Promoting Its Resilience during Inflammation

Abstract: Bacteroidetes are an important group of anaerobic bacteria abundant both in the oral and gut microbiomes. Although iron is a required nutrient for most living organisms, the molecular mechanisms of adaptation to the changing levels of iron are not well known in this group of bacteria.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Nevertheless, comparative genomic analyses have shown that some gut commensals are also equipped (superoxide dismutases or reductases, PerR, rubrerythrins.) 53 , 54 , and measurements of antioxidative potential among Bifidobacteriaceae and lactic acid bacteria have revealed the ability of certain strains to inhibit lipoperoxidation in vivo and in vitro using liposomal suspensions 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, comparative genomic analyses have shown that some gut commensals are also equipped (superoxide dismutases or reductases, PerR, rubrerythrins.) 53 , 54 , and measurements of antioxidative potential among Bifidobacteriaceae and lactic acid bacteria have revealed the ability of certain strains to inhibit lipoperoxidation in vivo and in vitro using liposomal suspensions 55 .…”
Section: Discussionmentioning
confidence: 99%